MODERASI BERAGAMA DALAM PERSPEKTIF HABITUS PIERRE BOURDIEU DAN TAFSIR KEBUDAYAAN CLIFFORD GEERTZ - Yeni Susanti (Habitus: Jurnal Pendidikan, Sosiologi, & Antropologi, 2024)
This research is motivated by ethnicity, race, religion, language, and life values in Indonesia which often give rise to various conflicts. One of Indonesia's unity which contains a potential threat to the country's unity is religion, so to avoid conflict and disharmonization it is necessary to foster a moderate, inclusive way of faith or an open religious attitude, which is called an attitude of religious moderation. This research will describe the results of the analysis of the implementation of various moderations from the perspective of Pierre Bourdieu's habits and Clifford Geertz's culture using a qualitative descriptive approach. The research subjects, who were then called informants, were obtained through a purposive sampling technique with the criteria that the informants were people who understood the concept and implementation of religious moderation in the city of Surakarta as well as the general public. Data sources consist of primary and secondary data. Primary data was obtained from data collection through interviews and observations, while secondary data was obtained through a literature study. Based on the results of data analysis, it is explained that religious moderation is understood as a balanced religious attitude between the practice of one's religion (exclusive) and respect for the religious practices of other people with different beliefs (inclusive) which becomes a guideline for the behavior of every religious community which then becomes culture as per Clifford Geertz's concept of culture. Religion is a whole of knowledge that is passed down from generation to generation in symbolic form or what Bourdieu calls habitus that resides in the mind of the actor (individual). Keywords: religious moderation, habits, culture ABSTRAK Penelitian ini dilatarbelakangi oleh keragaman etnis, suku, ras, agama, bahasa dan nilai-nilai hidup yang ada di Indonesia sering berbuntut berbagai konflik. Salah satu keragaman Indonesia yang mengandung potensi ancaman bagi persatuan negara adalah agama, maka untuk menghindari konflik dan disharmonisasi perlu ditumbuhkan cara beragama yang moderat, inklusif atau sikap beragama yang terbuka, yang disebut sikap moderasi beragama. Penelitian ini akan mendeskripsikan hasil analisa implementasi moderasi beragama dari preskpektif habitus Pierre Bourdieu dan kebudayaan Clifford Geertz dengan pendekatan kualitatif deskriptif. Subjek penelitian yang kemudian disebut dengan informan diperoleh melalui teknik purposive sampling dengan kriteria bahwa informan adalah orang yang memahami konsep dan implementasi moderasi beragama di Kota Surakarta serta masyarakat umum. Sumber data terdiri dari data primer dan sekunder. Data primer diperoleh dari hasil pengumpulan data melalui wawancara dan observasi, sementara data sekunder diperoleh melalui studi literatur. Berdasarkan hasil analisis data dijelaskan bahwa moderasi beragama dipahami sebagai sikap beragama yang seimbang antara pengamalan agama sendiri (eksklusif) dan penghormatan kepada praktik beragama orang lain yang berbeda keyakinan (inklusif) menjadi pedoman berperilaku setiap umat beragama yang kemudian menjadi kebudayaan sebagaimana konsep budaya Clifford Geertz. Agama sebagai keseluruhan pengetahuan yang diwariskan dari generasi ke generasi dalam bentuk simbolik atau yang oleh Bourdieu disebut sebagai habitus yang berada di dalam pikiran aktor (individu). Kata Kunci: moderasi beragama, habitus, kebudayaan